Pengaruh Strategi Perusahaan, Kematangan Teknologi Informasi, dan Ukuran Perusahaan terhadap Respon Strategik dalam Menghadapi Globalisasi - Neni Meidawati (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2004)
This research examined effect beetween corporate strategy, information technology maturity and firms’ size with strategic response to globalization reflected by the firm for willingness to increase the information technology investment.Collected data with mail survey to manager/top management financial services company as decision maker. Statistic method was multiple regression and chi-square used to examine hy¬pothesis. Base on the data was collected for 37 respondent this research find that corporate srate¬gy and three variabel information technology maturity as control information technology, organiza¬tion information technology, and integration information technology are not effect with decision top management/manajer for willingness to increase the information technology investment, and then firms’ size not afected with that decision. Only one variabel affected, there is planning information technology as one for variabel information technology maturity.Key words: Globalization, free trade, strategic response, corporate strategy, information technology ma¬turity, firms’ size.